PERAN ORANGTUA DALAM MENDAMPINGI PUBERTAS REMAJA DENGAN AUTISME DI SEKOLAH LUAR BIASA PEMBINA PEKANBARU - Buyani, Olvi Septia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Adolescence is a phase when there is an identity crisis. This is experienced by adolescents with autism. During adolescence, there will be physical, psychological, and emotional changes. Adolescents with autism will experience confusion because adolescence is a transitional period towards adulthood. The purpose of this study is to explore the role of parents in assisting adolescents with autism while puberty. Methods: This study is a qualitative descriptive study using a phenomenological approach. This study was conducted at SLB Pembina Pekanbaru. The population in this study are parents who have adolescents with autism who are experiencing puberty and are currently studying at SLB Pembina Pekanbaru. The sample in this study was taken using a purposive sampling method with a total of 6 participants. Collecting data using in-depth interviews and observation. The collected data were analyzed using the Colaizzi method. Results: The results of this study obtained 4 (four) themes, namely (1) Parental perception related to puberty of adolescents with autism, (2) Knowledge of parents regarding puberty of adolescents with autism, (3) The role of parents about puberty and sexual education to adolescents with autism and (4) The role of parents in instilling religious values in adolescents with autism. Conclusion: This study concluded that adolescents with autism really need to be given more appropriate assistance to make them human beings who are independent and can better control their sexual behavior.